Intra-European Unions and Their Role in the Settlement of International Conflicts (International relations and international law Journal, 2023)
The formation of the Lublin Triangle occurred on July 28, 2020. The historical value of the issue of actualizing the mediation role of the Lublin Triangle lies in the stated purpose of this Agreement - to resolve issues of political, economic and social cooperation.In order to achieve this goal, military units of the participating countries have been created for rapid response in a threat situation, cooperation has been established with other intra-European unions and associations - the Bucharest Group, the Minsk Group, for greater integration of Ukraine along the path chosen by it into the European Union and NATO. The article makes a historical digression into the era of the conclusion of the Union of Lublin and analyzes the perepetias of the entry of modern Ukrainian territories into the Commonwealth during its union with the Principality of Lithuania. Ukraine's attraction to alliances with its Western neighbors finds its historical continuity in the conclusion of this Agreement and has prospects for more successful implementation for the participating countries, creating new problems and challenges for Russia, the peoples that make up it, the integrity of their families, civil, cultural self-identification and determining the trajectory of life. This problem is relevant in the light of recent events in Europe.Key words: political, economical, military interaction, intermediary, commonwealth, union